Complex Interactions Between Large Igneous Province Emplacement and Global‐Temperature Changes During the Cenomanian‐Turonian Oceanic Anoxic Event (OAE 2). Issue 10 (12th October 2020) - Percival, L. M. E.; van Helmond, N. A. G. M.; Selby, D.; Goderis, S.; Claeys, P.
Abstract: Super greenhouse temperatures at the onset of the Cenomanian‐Turonian oceanic anoxic event (OAE 2) have been widely linked with large igneous province (LIP) volcanic activity. However, the extent to which volcanism influenced subsequent climate changes throughout OAE 2, such as global cooling during the Plenus Cold Event (PCE) early in the OAE, and the subsequent return to very warm conditions through the second part of the crisis remain less clear. Here, new osmium‐isotope ( 187 Os/ 188 Os) data are presented from the northeastern margin of the proto‐North Atlantic Ocean (ODP Leg 174AX Bass River, NJ, USA). The results are consistent with previously published OAE 2 records and are similarly interpreted as documenting LIP activity while further demonstrating the ability to use osmium‐isotope stratigraphy as a global chemostratigraphic marker in open‐ocean records. Correlations of 187 Os/ 188 Os and sea‐surface temperature trends at Bass River and other sites show that the earliest PCE cooling coincided with intense volcanism, but that LIP activity began to decline during or soon after the cold pulse. These temporal relationships support previous hypotheses that the PCE was regionally diachronous and likely caused by enhanced carbon sequestration via organic‐matter burial and silicate weathering, rather than a period of volcanic quiescence, while the persistently warm conditions later in OAE 2 were linked to reduced silicate weathering rather than sustained volcanism. These findings highlight the complex interactions between LIP emplacement and climate responses during OAE 2, reemphasizing the need for similar correlations between volcanism and paleotemperature proxy data for other major events in Earth's history. Key Points: Osmium‐isotope records of volcanism during OAE 2 are directly compared to paleotemperature records from the same sites for the first time Plenus Cold Event cooling is confirmed to have been diachronous and likely caused by enhanced CO2 drawdown rather than reduced volcanism High global temperatures were maintained during OAE 2 long after LIP activity declined, likely aided by reduced silicate weathering rates